DAWUD AL-DHAHIRI DAN ALIRAN AL-DAHIRIYAH - M. A. Tihami (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 1995)
Dawud al-Dhahiri dan Aliran al-Dhahiriyah